PERAN HUTAN KEMASYARAKATAN MELALUI INISIATIF KARBON TERHADAP NAFKAH RUMAH TANGGA PETANI DI KABUPATEN GUNUNG KIDUL DAERAH ISTIMEWA YOGYAKARTA Function of community forest on Carbon Initiative household income of the farmers in Gunung Kidul Yogyakarta - Deasy Fitria; Arya Hadi Dharmawan; Lilik Budi Prasetyo (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2017)
The community forestry (HKm) is a government effort to reduce greenhouse gas emissions in climate change mitigation strategies and improvement of community welfare. The objective of this research was to analyze carbon economy contribution to the household income that was attained from carbon initiative activities in the HKm. This study was conducted in the community forestry in Ngeposari village, Gunung Kidul district, Special Region of Yogyakarta. The methods of the research were deep interview, observation and document analysis. Descriptive analysis and scoring technique were applied to understand the income structure of the farmer household and an additional incentive from carbon economy by using several assumptions. Based on the three assumptions, this study revealed that the low household-level received the highest benefits from carbon initiative activities. Total carbon income from 155 ha was estimated to be 295 321 IDR based on VCM scheme calculation, if it was compared to the community business plan which included timber harvesting.Key words: Community Forest, carbon initiative, livelihood